Okay for now - Schmidt, Gary D. (Boston : Clarion Books, 2011)
As a fourteen-year-old who just moved to a new town, with no friends, an abusive father, and a louse for an older brother, Doug Swieteck has all the stats stacked against him until he finds an ally in Lil Spicer.
Companion to The Wednesday Wars.
Keywords: Audubon, John James, -- 1785-1851. -- Juvenile fiction; Families -- New York (State) -- New York -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Schools -- Juvenile fiction; Junior high schools -- Juvenile fiction; Friendship -- Juvenile fiction; Theater -- New York (State) -- New York -- Juvenile fiction; Coming of age -- Juvenile fiction; Broadway (New York, N.Y.) -- Juvenile fiction; Humorous fiction